Analisis Perilaku Konsumen dan Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Sayur organaik Institut Pertanian Bogor di Pasaran Modern Kota Bogor - Al-amro, Imroatu Haiyin; Setiadi, Agus; Roessali, Wiludjeng (JURNAL AGRICA, 2025)
Organic agriculture in Indonesia had significant growth in 2022, the area of organic agriculture is 261,400 Ha. One of the units of businesses that develop organic vegetables in the Bogor is a Badan Pengelola Bisnis dan Wakaf Institut Pertanian Bogor (BP Biswaf IPB). This trend in healthy lifestyle provides an opportunity for organic vegetable entrepreneurs, Although the challenges in marketing are getting tighter because of the number of competitors. Consumers are now more intelligent and  more selective before making a purchase decision is influenced by knowledge, confidence, and motivation for organic products. The study aims to analyze consumer behavior and the marketing effect on the purchase of organic vegetables at the Institut Pertanian Bogor in the modern market city of Bogor. The method of study used is a survey of data collected through questionnaires distributed to 210 responders and using a scale Likert. Data analysis is carried out using multivariate structural equation modeling (SEM) to know the relationship between the psychological factor variables composed of motivation, Perception, The marketing and marketing approaches that make up the product, Price, Location, Promotion, People, physical means and process with the purchase decision. Results of research show that motivation and perception have a positive and significant influence on purchasing decisions and Products, Location, Promotion, People, and Process also has a positive and significant influence on the decision to purchase organic vegetables. There are three variables, physical means, and prices do not affect the purchase decision. This finding provides insight for entrepreneurs in designing more effective marketing strategies to increase organic vegetable sales in the modern market.This research is expected to contribute to the development of sustainable marketing policies for organic products as well as raise public awareness of the importance of.